KETERLIBATAN AYAH DALAM PENGASUHAN (FATHER INVOLVEMENT) DAN DAMPAKNYA TERHADAP PREFERENSI PEMILIHAN PASANGAN HIDUP PADA PEREMPUAN DEWASA AWAL - Ratu Venny Ramadhania; Lenny Wahyuningsih; Evi Afiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Father involvement in parenting is a crucial yet often overlooked aspect of family dynamics in Indonesia, where fathers are predominantly perceived as breadwinners rather than active caregivers. This study aims to explore the experiences of early adult women regarding their fathers’ involvement in parenting and its impact on their partner selection preferences. A qualitative approach with a case study design was employed, conducted at the Faculty of Teacher Training and Education (FKIP) of Sultan Ageng Tirtayasa University. Four primary informants aged 20–22 years were selected through purposive sampling, along with four supporting informants (biological parents). Data were collected through semi-structured in-depth interviews, 14-day daily observations, and source triangulation, then analyzed using thematic analysis. The findings reveal that father involvement in all four informants was categorized as high, encompassing three dimensions: engagement (active interaction and meaningful communication), accessibility (physical and psychological availability), and responsibility (comprehensive fulfillment of needs and value guidance). Partner selection preferences included responsibility, religiosity, communication quality, physical-emotional closeness, and value congruence. Father involvement was found to shape these preferences through two mechanisms: internalization of positive relational experiences and compensation for relational limitations. These findings align with Bowlby’s attachment theory through the concept of internal working models and Bandura’s social learning theory, both of which confirm that early relational experiences with the father figure form an individual’s internal representations in determining partner criteria in adulthood.